2007
DOI: 10.1075/intp.9.1.05lop
|View full text |Cite
|
Sign up to set email alerts
|

Predicting proficiency in signed language interpreting

Abstract: An empirical study was designed to identify which perceptual-motor, cognitive and personality factors may underlie both acquisition of a signed language as a B language and development of signed language interpreting skills. If abilities that are potentially needed are found, a previous assessment of candidates' potential for developing signed-language interpreting skills could be useful in identifying which students are likely to obtain good results during training. Perceptualmotor and cognitive skills, perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 12 publications
0
18
1
2
Order By: Relevance
“…These include effects of age (Bergfield-Mills & Jorden 1980) and visual processing (Gomez et al 2007;Kyle & Woll 1985;Kyle et al, 1981). Further, given that Pfanner (2000) observed a significant correlation between L2 anxiety and end of course grade, it is surprising that in the current study confidence levels in passing the course did not show a significant relationship with exam success.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…These include effects of age (Bergfield-Mills & Jorden 1980) and visual processing (Gomez et al 2007;Kyle & Woll 1985;Kyle et al, 1981). Further, given that Pfanner (2000) observed a significant correlation between L2 anxiety and end of course grade, it is surprising that in the current study confidence levels in passing the course did not show a significant relationship with exam success.…”
Section: Discussioncontrasting
confidence: 51%
“…Such contact with signers is likely to be to the learners' benefit. Gomez et al (2007) tested the relationship between five aspects of personality (social introversion, self-strength, dependence, dominance and social responsibility) and success at learning LSE and found that only dominance was related to success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to verify the test validity, aptitude test scores were correlated with proficiency at interpreting exams and at final exams; to verify the test reliability, aptitude test results were scored by means of criteria that were claimed to be objective and therefore replicable. A preliminary consideration is that all these studies 11 do not generally have large sample sizes by commonly accepted scientific standards: 19-29 subjects (Gerver et al 1984), 28 subjects (López Gómez et al 2007), 83 subjects, reduced to 57 (Moser-Mercer 1985), 46 subjects (Russo & Pippa 2004). However, they have been able to detect some statistically significant predictors.…”
Section: Predictive Aptitude Testsmentioning
confidence: 95%
“…However, they have been able to detect some statistically significant predictors. Let us now consider the main features of these studies and their main results, starting from the contribution on aptitude for sign language interpreting (López Gómez et al 2007). …”
Section: Predictive Aptitude Testsmentioning
confidence: 99%